Psychopharmacology: From serendipitous discoveries to rationale design, but what next?. (November 2018) - Robinson, Emma
Psychopharmacology really developed as a discipline from the mid-20th century with the discovery of a number of new classes of psychoactive drugs which could modify behaviour. These drugs were discovered as a consequence of clinical observations of patients, often being treated for other conditions. These serendipitous discoveries were the start of an era of drug development which has led to the antidepressants, antipsychotics, anxiolytics and mood stabilisers used today. Subsequent research focused on understanding why these drugs were effective, and used this information to develop a second generation of drugs that were more selective for their therapeutic targets, and therefore had reduced side effects and improved safety and tolerability. After a period of decline in new discoveries and withdrawal of the majority of the major pharmaceutical companies from active development programmes in psychiatry, new avenues are emerging fuelling renewed interest in this area.